Pengaruh Penambahan Minyak Selasih (Ocimum basilicum) sebagai Atraktan Pada Kertas Perekat Lalat Terhadap Jumlah Lalat yang Tertangkap - Dwi Afria Tuti; Sarjito Eko Windarso; Siti Hani Istiqomah (Poltekkes Kemenkes Yogyakarta, 2012)
The existence of flies in traditional markets may support the spreading of diseases which are caused by this vector insect. One of the controlling methods is to add selasih ((Ocimum basilicum) oil onto fly adhesive paper. This method is environmentally friendly and specifically only affect the flies target. The study was aimed to understand the influence of the selasih oil towards the number of trapped flies at Telagareja Market of Gamping, by conducting an experiment with post-test only with control group design. The number of trapped flies were analysed statistically by one way anova test. The results showed that the addition of selasih oil as sex attractant in 0,4 ml, 0,5 ml and 0,6 ml could collect flies in average of 20, 30 and 38 respectively. Meanwhile, in the control group, i.e. the common red plastic fly adhesive straw only able to attract 9 flies in average.